Control of Grid Connected Modular Multilevel Converter - Blahnik, Vojtech; Kosan, Tomas; Talla, Jakub (Elektronika ir Elektrotechnika, 2015)
This paper describes the control of multilevel voltage source active rectifier connected directly to ac grid. The proposed topology of multilevel converter is composed of three cascaded H-bridge converters (CHB), thus in this case seven level converter. Designed control algorithm provides direct current control in each phase even under unbalanced load. The main attention is paid to voltage balancing of the individual power cells (H-bridge). The voltage balancing algorithm is designed separately for each power cell. The paper presents simulation and experimental results of designed low-voltage laboratory prototype with rated power of 10 kW. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12777